Role of the Financial Service Authority of the Republic of Indonesia in Determining Financial Technology Crime as Bijzondere Toestanden - Suseno, Jarot Jati Bagus; Mahita Paksi, Tutut Ferdiana; Yusriando, Yusriando (Al-Bayyinah, 2024)
Changes in civilization through information technology have also brought changes to the world of financial administration, including fund lending institutions. The change is demonstrated by the presence of financial technology (fintech). The progress of the digital financial world, including fintech institutions in the country, needs to be balanced with adequate legal policies regarding implementing online lending by fintech. This has given rise to various problems, including criminal matters through fraud and threats from fintech institutions and online loans. Regarding this, the Financial Services Authority of the Republic of Indonesia (OJK), the authorized institution for handling fintech issues that lead to criminal matters, is not yet optimal. This doctrinal method article aims to discuss topics related to the urgency of the role of the Financial Services Authority in handling fintech crimes. Based on existing studies, the OJK, the party responsible for fintech criminal matters, has been unable to supervise and protect fintech users. This is the basis for the need to create a formulation regarding supervision and action through criminal law, specifically against fintech institutions that are illegal and commit actual unlawful acts, where the law enforcement agency is the OJK, which partners with law enforcement agencies in the context of state primary constitutional organs and enforcement agencies which has the status of a state auxiliary organ.